A Review of Hydraulic Pressure for Water Supply Unites Considering Iraqi Geodetic Reference - Noora Akeel; Mustafa Tariq Mustafa; Muntasir Abdl Hameed; Corina Boncescu (Journal of Techniques)
The hydraulic pressure head of the flowing water (between the entrance and exit pipes) in water distribution networks depends on the length and the slope of these pipes, which can represent the head losses for each meter length, where the slope and length of the water supply network pipes are dependent on specified datum ground elevations. This ground elevation may result in a reduction in head losses with hydraulic grade pressure. As a result, the precision of the measured data used to observe ground elevations is critical to decrease the error of these losses and apply an accurate local reference. It's critical to comprehend the implications of using Geographic Information System (GIS) application technology for water distribution network models to evaluate the hydraulic grade head with Iraqi Geodetic Reference. These GIS input data are based on an analysis of the relationship between selected spatial data resolution and the precision of the expected hydraulic head for selected stations with a distribution network. This research aims to review the literature and try to track the conversion of geodetic references and datums to accurately identify the hydraulic pressure for the selected locations of the water supply network. It was found that recent researches tend to use GIS application to create novel methods to reduce head losses and error.